The HASTE Protocol: a standardised CT Coronary Angiography service operated from a District General Hospital. Issue 2 (11th July 2018) - Parsons, Iain Thomas; Bannister, Clare; Badelek, John; Ingram, Mark; Wood, Emma; Horton, Alex; Hickman, Michael; Leatham, Edward
Abstract : Introduction: CT coronary angiography (CTCA) has excellent sensitivity but lacks specificity when compared with invasive coronary angiography (ICA) particularly in patients with a high coronary calcium burden. CTCA has been shown in large trials to decrease the requirement for diagnostic ICA and provide diagnostic clarity. We describe the methodology used to provide a standardised CTCA service established in a District General Hospital, which may assist other hospitals aiming to develop a cardiac CT service. Methods: Scan request forms, authorisation and patient instruction were recorded. Patient preparation prior to CTCA as well as exclusion and inclusion criteria were documented. Scans were interpreted using a multidisciplinary team (MDT) approach in order to organise follow-up, medication and further investigation. Results: Over 6 months, 157 consecutive scans were performed. CTCA was completed in 88% (n=138/157) and considered of diagnostic quality in 82% (n=129/157). The median radiation dose was 3.42 mSv. Overall, 64% of patients had evidence of coronary calcium. Following MDT review, 72% (n=113/157) of patients were discharged without requiring invasive angiography. 15% (n=24/157) of patients went on to have invasive angiography showing non-obstructive disease and 13% (20/157) of patients underwent percutaneous coronary intervention (11%) or bypass surgery (1%). Discussion: Appropriate referrals, patient preparation and scan quality remain significant factors in running a CTCA service. Despite this, the vast majority of patients can be discharged on the basis of the CTCA alone. An MDT approach is key to the delivery of a cardiac CT service.